Fe-Ga multiple bonding? Synthesis, spectroscopic and structural characterization of a transition metal complex containing a cationic two-coordinate gallium centre. - Bunn, N; Aldridge, S; Coombs, D; Rossin, A; Willock, D; Jones, C; Ooi, L (2004)
This communication reports the synthesis and characterization of the cationic iron complex [((eta5-C5Me5)Fe(CO)2))2Ga]+[BAr(f)4]- [Ar(f) = C6H3(CF3)2-3,5] containing a symmetrically bridging two-coordinate gallium atom and a delocalised Fe-Ga-Fe pi system incorporating partial Fe-Ga multiple bond character.